CHARACTER EDUCATION REINFORCEMENT IN EFL CLASSROOM - Zelvia Liska Afriani (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2019)
This study aims at discussing the needs of character education reinforcement in EFL (English as a Foreign Language) Classroom. Character education plays an important role in developing students’ affective education which is concerned with faith, affections, justice, politeness, morality, responsibility, and attitudes. Recently, Indonesian education is facing a degradation dealing with students’ behaviour. Some examples that can be observed nowadays are bullying, gang fighting, sexual harassment, and robbing. Such manners need to be controlled and prohibited. Therefore, English teachers who take a part in the classroom should also help their students in overcoming this situation by way of reinforcing character education in teaching and learning process. The condition shows that English teachers are required to reinforce and engage the values of character education as one of the significant aspects that essentially be considered in order to make Indonesian education have a good quality.